GRAVIMETRIC DETERMINATION OF SULPHATE IN SOME SELECTED INDUSTRIAL EFFLUENTS (FUDMA JOURNAL OF SCIENCES, 2021)
Gravimetric Analysis as one of the Analytical method for the Quantitative Determination of sulphate ions from aqueous media being the most simplest, rapid and low-cost method. This study evaluates some selected parameters and the results were compared with some regulatory standard; Federal Ministry of Environment (FME) in Nigeria and the World Health Organization. The Concentration of the selected industrial effluent was determined using the aforementioned method. The values of Density, TSS and TS were in the range of 0.950 g/ml – 0.976 g/ml, 67 ppm – 2051 ppm and 728 mg/L- 2700 mg/L respectively. While the percentage of sulphate obtained from each sample were 14.65%, 7.35%, 6.19, 17.93% and 29.01% for NASCO, DANA, KRPC, NILEST and KCV respectively. A new technological treatment process is recommended for these industries to provide good ways on waste management that are economically viable.
Keywords: Sulphate Ion, Industrial Effluent and Gravimetric method